PENYULUHAN TENTANG GIZI SEIMBANG UNTUK IBU HAMIL DALAM PENCEGAHAN DINI STUNTING - Syamsuryanita,; Irmawati,; Nurul Ikawati, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of the implementation of making cassava sticks is to increase income in the midst of the Covid-19 pandemic, provide solutions to overcome unemployment and create new innovations in the field of selling snacks. This research was conducted in December 2021 at Jalan. Patumbak Defense, Deli Serdang Regency, North Sumatra. to manage the digital media. From the results obtained in this activity, it is suggested that the use of this digital marketing strategy can be followed up with regular guidance so that it can be effective and optimal in supporting marketing activities and increasing MSMEs business sales.